Strategi Komunikasi Dalam Pembinaan Tahfidz Al-Qur’an Santriwati Asrama An-Nadhloh Pondok Pesantren Darussalam Blokagung - Maskur; Hasyim Iskandar; Diana Intan Alkanzu (JDARISCOMB: Jurnal Komunikasi dan Penyiaran Islam, 2025)
The purpose of this research is to find out the communication strategy used in the development of tahfidz al-qur'an for students of the an- nadhloh dormitory of the Darussalam Blokagung Islamic boarding school and to know the factors that are obstacles and supporters in memorizing the al-qur'an for students of the an-nadhloh dormitory of the darussalam blokagung Islamic boarding school. The type of research used by researchers is qualitative research. This research is classified into the type of field research. The approach used by researchers is a descriptive approach. To test the validity of the data Researchers use observational extensions, increasing persistence and triangulation. All data that has been collected in the analysis uses data collection analysis, data reduction, data appearance, and inference. The communication strategy used in the Development of Tahfidz Al-Qur'an for Santriwati Dormitory An-nadhloh Pondok Pesantren Darussalam Blokagung is in accordance with Pace and Faules theory where the communication strategy consists of three main goals, namely (a) To secure understanding, namely ensuring that the communicant understands the message received. If he can understand and accept, then the acceptance must be fostered. (b) To establish acceptance, that is, after the communicant understands and receives the message, this message must be fostered. (c) To motivation action, that is, after the acceptance is fostered, this activity must be motivated. Factors that become obstacles and supporters in memorizing the Al-Qur'an, students of the An-Nadhloh Dormitory at Pondok Pesantran Darussalam Blokagung not only from internal but also external roles that include family and environment also affect in memorizing the Al-Qur'an for students.